'Good' and 'bad' doctors - a qualitative study of the Austrian public on the elements of professional medical identity. Issue 1 (31st December 2022) - Grundnig, Julia S.; Steiner-Hofbauer, Verena; Katz, Henri; Holzinger, Anita
ABSTRACT: Professional identity formation has become a key focus for medical education, but there is still much to learn about how to help students develop their professional identity. At a time when influential concepts such as public- and patient-centered care have become common values, there is little research on the conceptions of the public that trainees might adopt during their training. Defining characteristics of 'good' and 'bad' physicians can be a starting point when considering how to incorporate aspects of professional behavior into medical curricula. Therefore, this study examined the essential elements of physician identity from the public's perspective. This study aimed to describe the Austrian public's viewpoint about the characteristics of 'good' and 'bad' doctors. Using a qualitative research design, interviews were conducted with the Austrian public (n = 1000, mean age 46.4 ± 15.8 years). Interviews were transcribed verbatim and analyzed via qualitative content analysis. The respondents stated 2078 answers for 'good' and 1728 for 'bad' doctors. The content analysis produced seven categories: 'social skills' (36.3%), 'professional competence' (30.2%), 'personality' (10.8%), 'communication' (6.3%), 'practice organization' (5.9%), 'ethical and moral behavior' (5.7%), and 'I do not know, or I have no idea' (4.9%). The public can help medical students to construct their professional identity by supporting the exploration of and commitment to professional values that society expects of physicians. Ideally, fusing medical expertise with social skills will fulfill the ideal of what the public considers a 'good' doctor. This shared definition of a 'good physician' has several implications for medical education. Future physicians can benefit from education about the general population's medical needs as well as personal needs, fears, and concerns.